Plasma Membrane Targeting of Protocadherin 15 Is Regulated by the Golgi-Associated Chaperone Protein PIST - Hongyun Nie; Yueyue Liu; Xiaolei Yin; Huiren Cao; Yanfei Wang; Wei Xiong; Yushuang Lin; Zhigang Xu (Neural Plasticity)
Protocadherin 15 (PCDH15) is a core component of hair cell tip-links and crucial for proper function of inner ear hair cells. Mutations of PCDH15 gene cause syndromic and nonsyndromic hearing loss. At present, the regulatory mechanisms responsible for the intracellular transportation of PCDH15 largely remain unknown. Here we show that PIST, a Golgi-associated, PDZ domain-containing protein, interacts with PCDH15. The interaction is mediated by the PDZ domain of PIST and the C-terminal PDZ domain-binding interface (PBI) of PCDH15. Through this interaction, PIST retains PCDH15 in the trans-Golgi network (TGN) and reduces the membrane expression of PCDH15. We have previously showed that PIST regulates the membrane expression of another tip-link component, cadherin 23 (CDH23). Taken together, our finding suggests that PIST regulates the intracellular trafficking and membrane targeting of the tip-link proteins CDH23 and PCDH15.